The political voice of diaspora: An analysis of external voting of Moldovan migrants - Rosca, Alla (Journal of Eastern European and Central Asian Research (JEECAR), 2019)
The study examines the voting preferences of Moldovan diaspora in the 2014 parliamentary elections. The paper aims to determine which political or economic circumstances in the host country have the biggest impact on determining voting preferences of the migrants. The political favorites of the Moldovan diaspora differ from those of their domestic counterparts. Furthermore, there are essential differences in voting patterns among migrants living in different countries. The findings suggest the migrants’ voting behavior is affected in some way by the political and economic realities of the host countries. The voting preferences of voters of the left and right wing parties are mostly affected by the political and socio-economic realities of the country of residence, although members of the diaspora voting for centrist parties are not affected by those factors.